THE EFFECT OF LEXICAL INFERENCING STRATEGIES ON STUDENTS’ READING COMPREHENSION - Juliana Juliana (Journal MELT (Medium for English Language Teaching), 2018)
This study was conducted to investigate the effect of lexical inferencing strategies on students’ reading comprehension. This study was aimed was to find out whether the use of lexical inferencing strategies had effect on students’ reading comprehension. The population of this study was 90 Informatics Engineering students of Potensi Utama University in the fifth semester of 2014-2015 academic year. A placement test was given to 90 students to select 60 similar English proficiency level students. The instruments used for collecting data were written test and spoken test. These tests were conducted to identify students’ reading comprehension performance toward lexical inferencing strategies. These data were analysed by applying an experimental research design involving pre-test and post-test which were administered for control and experimental groups. The control group was taught by using conventional method, while the experimental group was treated by using lexical inferencing strategies. The results of the test showed that the use of the lexical inferencing strategies had significantly affected to students’ reading comprehension performance. Hence, it was concluded that lexical inferencing strategies was recommended to improve the students’ reading comprehension performance.